Enhancing Spiritual Character Development through Al-Ghazali's Sufi Pedagogy and Canva-Based Learning Media - Sarah Nur’aeni Khoiriyah; Alief Budiyono; M Slamet Yahya (Journal of Innovation and Research in Primary Education, 2026)
The rapid advancement of digital technology has precipitated moral decline among youth, necessitating innovative approaches to spiritual education. This study examines the integration of Al-Ghazali's Sufi pedagogy with technology-based learning media in Islamic religious education. A qualitative case study was conducted at MTs Cokroaminoto Madukara, Banjarnegara, Indonesia. Data were collected through systematic observation and documentation of religious activities, including daily Quranic recitation, congregational prayers, memorization programs, and Canva-based learning implementations. Analysis employed the Miles and Huberman framework involving data reduction, display, and conclusion drawing. Findings revealed systematic integration of Al-Ghazali's core Sufi values—tawakkal, zuhud, and ihsan—through structured religious activities enhanced by Canva-based digital media. Measurable improvements included 23% increase in memorization accuracy, 17% rise in voluntary religious participation, and enhanced ability to articulate connections between religious texts and daily life applications (78% compared to previous 54%). Technology-enhanced sessions demonstrated higher attendance rates (94.3%) compared to traditional lectures (89.7%). Unexpected outcomes included organic collaborative learning dynamics and digital literacy development. The findings demonstrate successful synergy between classical Islamic spiritual pedagogy and contemporary educational technology. Al-Ghazali's experiential Sufi approach, when mediated through interactive digital platforms, effectively engages digital native learners while cultivating authentic spiritual character development, challenging dichotomies between traditional religious education and technological innovation.